دور الوالين في تربية الأولاد - Hanisah Bt Husain; حنيسه بنت حسين (Universiti Sains Islam Malaysia, 2022)
In this academic project paper, the writer chooses the title of " A responsibility of parents in educating their children". The title was chosen because the writers want to know a responsibility of parents in the process of children education deeply. Good education will contribute to produce good or success generation either to their religion or country. According to the research, the writer used library references, Internet, observation, and some document, which relate to the research and get the needed information. At the last, the writer knows an importance of parent's responsibility in education their children to be succeeding people in their world and in the hereafter.